Urban Transport Services in Sub-Saharan Africa : Improving Vehicle Operations - World Bank (Washington, DC, 2014)
The report presents findings, and the way forward in respect of the Knowledge and Research (KAR) Project on vehicle operations in Sub-Saharan Africa, basically undertaken in Uganda and Ghana. In the first phase, the study identified problems faced by transport operators in both countries, and analyzed their impact on vehicle operating costs, as well as examining transport regulations, and current organization of transport services and their impact on vehicle utilization. In the second phase, to disseminate research findings, raise awareness, and develop action plans, a national stakeholder workshop was organized in each country. Main findings in Uganda highlight the need to introduce competition, through initiatives in the management of vehicle technical control, training assistance, and transport as a whole, involving the private sector. Similarly, in Ghana, highlights include the need to establish professional freight agents concerning land transport, in order to consolidate freight transport, in addition to improved arrangements in transport management, and transport legislation, and regulations. The two main focus areas are: support to local governments in the establishment of a transport operations strategy framework, and, specifically, support for the development, and management of bus, and truck parks.